Integrated Proteomic and Metabolomic Analyses of Chicken Ovary Revealed the Crucial Role of Lipoprotein Lipase on Lipid Metabolism and Steroidogenesis During Sexual Maturity - Cui, Zhifu; Ning, Zifan; Deng, Xun; Du, Xiaxia; Amevor, Felix Kwame; Liu, Lingbin; Kang, Xincheng; Tian, Yaofu; Wang, Yan; Li, Diyan; Zhao, Xiaoling (Frontiers in Physiology, 2022)
During sexual maturation and ovulatory cycle in chickens, ovaries undergo dynamic morphological and functional changes. The aim of this study was to evaluate the integrated proteome and metabolome analyses of chicken ovaries to characterize the changes in protein and metabolite profiles during sexual maturity. The ovary of Rohman layers before (125 days of age) and after (139 days of age) sexual maturation were collected for proteome and metabolome sequencing. The results showed that a total of 680 differentially expressed proteins (DEPs) and 1046 differential metabolites (DMs) were identified in the chicken ovary during sexual maturity. Among the DEPs, 595 proteins were up-regulated and 85 were down-regulated, whereas 519 metabolites were up-regulated and 527 were down-regulated. KEGG pathway enrichment analysis showed that DEPs were significantly enriched in glycerolipid metabolism, calcium signaling pathway, folate biosynthesis, fat digestion and absorption, NF-kB signaling pathway, and PPAR signaling pathway. However, DMs were significantly enriched in the metabolism pathways, PPAR signalling pathway, glycerolipid metabolism, ferroptosis, biosynthesis of amino acids, and biosynthesis of unsaturated fatty acids. The results of the integrated analyses of DEPs and DMs revealed that the PPAR signaling pathway and glycerolipid metabolism were the most significantly enriched pathways. Among the identified DEPs, lipoprotein lipase (LPL) was upregulated in sexually mature chicken ovaries and was significantly enriched in the glycerolipid metabolism pathway, which may partially explain the possible reasons for steroidogenesis and lipid reserves responsible for oocyte maturation and ovarian follicle development during sexual maturity in chickens. The results further revealed that LPL silencing decreased the content of lipid droplets (LDs), as well as the mRNA expression of lipid metabolism-related genes including; sterol regulatory element binding protein-1 (SREBP-1) and fatty acid synthase (FASN); and steroidogenesis-related genes such as; cytochrome P450 11A1 (CYP11A1) and steroidogenic acute regulatory (StAR). The present study revealed that upregulation of LPL in the chicken ovary during sexual maturity promotes granulosa cell (GC) lipid metabolism and steroidogenesis. These findings provide a theoretical support for further studies to elucidate the mechanism of lipid metabolism to regulate the function of avian GCs during sexual maturity in chickens.